Desenvolvimento de um mecanismo dosador de sementes e fertilizantes de disco horizontal - Silva, João Batista da (2025)
The use of electric motors to drive seed and fertilizer metering mechanisms has demonstrated greater efficiency when compared to the traditional ground wheel-driven systems used in agricultural implements. Furthermore, the use of a single mechanism for dispensing different inputs offers advantages such as operational space optimization and simplification of maintenance routines during sowing operations. In this context, the objective of the present study was to develop a prototype of a seed and fertilizer metering device equipped with a horizontal disc, driven by an electric motor. The study was conducted at the Laboratory of Agricultural Automation and Robotics, in Fortaleza, Brazil, where the design process, manufacturing of parts using 3D printing technology, and testing under controlled laboratory conditions were carried out. A completely randomized design was adopted in a 5×2×2 factorial scheme, consisting of five disc rotation speeds, two seed reservoir levels, and two fertilizer reservoir levels, aiming to quantitatively evaluate the performance of the mechanism, followed by a qualitative assessment through a seed germination test. The results showed that the metering system operated satisfactorily at rotation speeds of 2.45, 4.90, 7.35, and 9.80 rpm, and also allowed the identification of the influence of different reservoir load levels on the mechanism's performance. Nevertheless, the device demonstrated technical feasibility for practical application and presents potential for refinement and improvement in future versions.